2022
DOI: 10.3390/nu14091773
|View full text |Cite
|
Sign up to set email alerts
|

A Low Glycemic Index Mediterranean Diet Combined with Aerobic Physical Activity Rearranges the Gut Microbiota Signature in NAFLD Patients

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease, and its prevalence worldwide is increasing. Several studies support the pathophysiological role of the gut–liver axis, where specific signal pathways are finely tuned by intestinal microbiota both in the onset and progression of NAFLD. In the present study, we investigate the impact of different lifestyle interventions on the gut microbiota composition in 109 NAFLD patients randomly allocated to six lifestyle intervention groups: Low G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 68 publications
2
45
0
Order By: Relevance
“…Studies performed in nutrition and physical activity demonstrated that changes in dietary compositions and physical activity rates lead to improved clinical features, namely, liver enzymes and ultrasound changes in NAFLD [ 42 45 ]. Results from the present study showed that educational sessions could improve the clinical conditions of patients with NAFLD by affecting their lifestyle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed in nutrition and physical activity demonstrated that changes in dietary compositions and physical activity rates lead to improved clinical features, namely, liver enzymes and ultrasound changes in NAFLD [ 42 45 ]. Results from the present study showed that educational sessions could improve the clinical conditions of patients with NAFLD by affecting their lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies were performed to demonstrate the effects of specific diet and physical activity on improving NAFLD [ 42 45 ], all of which addressed the desired intervention within the study period. Accordingly, it was cost-effective in one educational-supportive study, as the strength of the study.…”
Section: Limitationsmentioning
confidence: 99%
“…Consequently, different microbiota alterations were observed according to the different lifestyles. For example, the abundance of Ruminococcus, Oscillospiraceae-UCG002, Oscillospiraceae-UCG005, Dialister, Alistipes, and Eubacterium eligens showed an increasing trend, whereas that of Collinsella showed a decreasing trend in LGIMD-ATFIS_1 intervention, which was not found in other groups (106). In addition, a randomized controlled trial revealed that microbial diversity deteriorates with increased hepatic fat content, while exercise and diet may help maintain the diversity of the gut microbiota (107).…”
Section: Lifestyle Interventionmentioning
confidence: 92%
“…Therefore, it is important to know not only the composition of foods, but also the effects that the different components produce in the body. It has been suggested that low-glycemic-load diets improve weight and fat mass loss compared to high-glycemic-load diets, and that reducing overall glycemic load is beneficial as an adjuvant in appetite regulation, in maintaining weight loss, and in controlling weight [ 76 , 77 , 78 ]. Even some important parameters of cardiovascular risk (such as triglycerides and HDL cholesterol) and the parameters of the “inflammatory state” of the organism, linked in multiple ways to the state of health, are favorably affected by the consumption of low-index foods and glycemic load.…”
Section: Extra Virgin Olive Oil Compoundsmentioning
confidence: 99%